Persepsi Kepala Desa tentang Kompetensi Pendamping Desa dalam Memfasilitasi Pembangunan Desa - Zahrial Syah Alam; Aida Vitayala. S Hubeis; Ninuk Purnaningsih (Agriekstensia : Jurnal Penelitian Terapan Bidang Pertanian, 2020)
The Ministry of Villages allocates special village funds for village development, which is facilitated by village facilitators by working together with the village head. Village facilitators are required to have a variety of basic competencies in accordance with the regulations of the village ministry, so that it becomes a benchmark for the success of the assistance activities. This paper aims to analyzes the influence of the characteristics of the village head, the interaction of the village head with the village assistant, and the village head's knowledge of the competency of the village assistant on the village head's perception of the competency of the village assistant in Nagan Raya districs. The results showed that the village head's working period would affect his perception of the competency of village facilitators, this was due to the high chance of interaction between the village head and the village facilitator, so the village head's perception of the competency of village facilitators was more positive.